Training, psychometric status, biological markers and neuromuscular fatigue in soccer - Selmi, Okba; Ouergui, Ibrahim; E Levitt, Danielle; Marzouki, Hamza; Knechtle, Beat; Nikolaidis, Pantelis T.; Bouassida, Anissa (Biology of Sport, 2022)
The study examined the relationship between psychometric status, neuromuscular, and biochemical markers of fatigue in response to an intensified training (IT) period in soccer. Fifteen professional soccer players volunteered to participate in the study (mean ± SD: age: 25 ± 1 years; body height: 179 ± 7 cm, body mass: 73.7 ± 16.2 kg, experience: 13.2 ± 3 years). Training load, monotony, strain, Hooper index and total quality recovery (TQR) were determined for each training session during a 2-week of IT. Counter-movement jump (CMJ) and biochemical responses [testosterone, cortisol, testosterone-to-cortisol ratio (T/C ratio), creatine kinase, and C-reactive protein] were collected before and after IT. Results showed that IT induced significant increases in cortisol, creatine kinase and C-reactive protein and significant decreases in T/C ratio and CMJ performance from before to after IT (p < 0.01, p < 0.001, p < 0.001, p < 0.01, p 0.05). Training loads were positively correlated with Hooper index (p < 0.05) and negatively correlated with total quality recovery (p < 0.05). Hooper index was positively correlated with cortisol (p < 0.05), T/C ratio (p < 0.01), and creatine kinase (p < 0.01), and negatively correlated with CMJ (p < 0.05). Furthermore, TQR was negatively correlated with T/C ratio (p < 0.01), creatine kinase (p < 0.001), and C-reactive protein (p < 0.05), and positively correlated with CMJ (p < 0.01). Neuromuscular fatigue, muscle damage, and change in the anabolic/catabolic state induced by the IT were related to well-being and perceived recovery state among professional soccer players.